Mapping evidence on predictors of adverse sexual and reproductive health outcomes among young women in South Africa: A scoping review - Obasanjo A. Bolarinwa (AOSIS, 2021)
Background: Globally, most young women have an unmet need for sexual and reproductive health (SRH), which remains a public health concern. Identifying the predictors can help reduce this challenge.